2006
DOI: 10.1093/cercor/bhl018
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Auditory Cortex Parallel Rapid Perceptual Learning

Abstract: Learning perceptual skills is characterized by rapid improvements in performance within the first hour of training (fast perceptual learning) followed by more gradual improvements that take place over several daily practice sessions (slow perceptual learning). Although it is widely accepted that slow perceptual learning is accompanied by enhanced stimulus representation in sensory cortices, there is considerable controversy about the neural substrates underlying early and rapid improvements in learning percept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
123
6
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(155 citation statements)
references
References 62 publications
20
123
6
1
Order By: Relevance
“…Other studies demonstrated growing evidence that the adult auditory cortex is a dynamic and adaptive processing center. This has been shown in auditory perceptual learning studies, in which long-lasting neuronal changes were observed in the auditory cortex of animals [45,46] and human beings [47,48] after intensive auditory training.…”
Section: Advances In Clinical Audiologysupporting
confidence: 53%
See 1 more Smart Citation
“…Other studies demonstrated growing evidence that the adult auditory cortex is a dynamic and adaptive processing center. This has been shown in auditory perceptual learning studies, in which long-lasting neuronal changes were observed in the auditory cortex of animals [45,46] and human beings [47,48] after intensive auditory training.…”
Section: Advances In Clinical Audiologysupporting
confidence: 53%
“…The authors assessed 11 adults with normal thresholds, using three suppressor stimuli: clicks, narrow band noise, and pure tones. It was found that the click and pure-tone stimuli were the most and least efective suppressors, respectively [47]. Speech, however, was not considered.…”
Section: Advances In Clinical Audiologymentioning
confidence: 99%
“…Current models propose that perceptual learning in adults depends strongly on top-down influences such as attention, reward, and task relevance. This demonstrates that the adult AC is a dynamic and adaptive processing center [9][10][11][12][13][14][15][16][17][18] . Natural auditory training occurs in job sectors involving frequent daily radio communications.…”
Section: Introductionmentioning
confidence: 83%
“…Although preexisting differences can influence musical activity and abilities, it is also clear that auditory abilities and their underlying neural substrates are highly malleable due to experience (e.g., Alain et al, 2007;Lappe et al, 2008). Thus, it is likely that although differences in personality or preexisting perceptual abilities might lead some individuals to choose to learn a musical instrument or play music video games, the actual experience of practicing these activities is what leads to differences in music aptitude.…”
Section: Discussionmentioning
confidence: 99%
“…The past two decades have nevertheless witnessed an abundance of reports suggesting that "musicians" outperform "nonmusicians" on measures of sensory, cognitive, and motor functions (Hannon & Trainor, 2007;Strait & Kraus, 2014). Studies with tightly controlled learning situations have demonstrated that remarkable behavioral and neural changes can occur as a result of auditory learning (e.g., Alain, Snyder, He, & Reinke, 2007;Lappe, Herholz, Trainor, & Pantev, 2008), or even passive exposure to musical stimuli (e.g., Hannon & Trehub, 2005). However, other evidence suggests that personality differences predict who undertakes music training and who does not (e.g., Corrigall, Schellenberg, & Misura, 2013).…”
mentioning
confidence: 99%